2017
DOI: 10.1007/s11011-017-9986-3
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic brain or retina? Visual psychophysical performance in diabetic patients in relation to GABA levels in occipital cortex

Abstract: Visual impairment is one of the most feared complications of Type 2 Diabetes Mellitus. Here, we aimed to investigate the role of occipital cortex γ-aminobutyric acid (GABA) as a predictor of visual performance in type 2 diabetes. 18 type 2 diabetes patients were included in a longitudinal prospective one-year study, as well as 22 healthy age-matched controls. We collected demographic data, HbA1C and used a novel set of visual psychophysical tests addressing color, achromatic luminance and speed discrimination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This is consistent with the study of Van Bussel et al . [ 47 ] showing that cognitive impairment in diabetes is related to higher GABA levels [ 47 ] and previous data showing that higher GABA/tCr levels were related to higher (worse) psychophysical thresholds [ 19 ] and lower brain activity as measured by the BOLD signal [ 48 ]. In fact, steady-state neurotransmitter levels may have distinct forms of biological impact (positive or negative), depending on the physiological system [ 49 ].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This is consistent with the study of Van Bussel et al . [ 47 ] showing that cognitive impairment in diabetes is related to higher GABA levels [ 47 ] and previous data showing that higher GABA/tCr levels were related to higher (worse) psychophysical thresholds [ 19 ] and lower brain activity as measured by the BOLD signal [ 48 ]. In fact, steady-state neurotransmitter levels may have distinct forms of biological impact (positive or negative), depending on the physiological system [ 49 ].…”
Section: Discussionmentioning
confidence: 97%
“…The pathophysiological effects of long-term glycemic disturbances in the central nervous system are still controversial. We had previously found that higher GABA levels were predictive of impaired psychophysical performance (speed and achromatic contrast discrimination) in T2DM, both at the time of evaluation and after one year [ 19 ]. However, the relation between changes in neurotransmission and chronic metabolic control remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual deficit-poor vision-was found to be rendered by loss of dendritic cell factor 1 through the GABA system in mouse primary visual cortex [56]. In the early stage of type 2 diabetes, occipital cortical GABA has been reported to be a novel predictor of visual psychophysical performance, that is, speed and achromatic discrimination thresholds [57]. The application of GABA and its agonist to senescent macaques lead to improved orientation and direction, an enhanced ability to signal visual stimuli, combined with decreased visual responsiveness and spontaneous activity [58].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it could be important to explore how distinct high‐caloric diet compositions, comprising different amounts of triglycerides and carbohydrates, may influence the rodent brain given that studies designed to investigate such impact are lacking. Also caution should be taken when attempting to generalize these findings to humans, although our previous work in humans highlights the functional relevance of measuring neurotransmitter levels in humans with metabolic disorders such as obesity and diabetes . Finally, we restricted the assessment of neurometabolic changes to the posterior hippocampus, because of the larger signal to noise ratios in this region.…”
Section: Discussionmentioning
confidence: 99%